Rapid and accurate identification and differentiation of Mycobacterium tuberculosis and non-tuberculous mycobacteria using PCR kits available in a high-burden setting - Castro-Rodriguez, Bernardo; Franco-Sotomayor, Greta; Rodriguez-Pazmiño, Ángel Sebastián; Cardenas-Franco, Greta Esther; Orlando, Solón Alberto; Hermoso de Mendoza, Javier; Parra-Vera, Henry; García-Bereguiain, Miguel Ángel (Frontiers in Public Health, 2024)
Infec@ons caused by mycobacteria, including Mycobacterium tuberculosis complex (MTBC) and non-tuberculous mycobacteria (NTM) are a major public health issue worldwide. Accurate diagnosis of mycobacteria species is a challenge for surveillance and treatment, par@cularly in high burden sejngs usually associated to low and middle income countries. In this study, we analyzed the clinical performance of two commercial PCR kits designed for the iden@fica@on and differen@a@on of MTBC and NTM, available in a high burden sejng like Ecuador. A total number of 100 mycobacteria isolates were included in the study, 50 of them previously characterized as M. tuberculosis and the other 50 characterized as NTM. Both kits displayed a great clinical performance for the iden@fica@on of M. tuberculosis, with 100% sensi@vity. On the other hand, for non-tuberculous mycobacteria, one of the kits displayed a good clinical performance with sensi@vity of 94% (CI 95%: 87-100%), while the second kit had a reduced sensi@vity of 75.6% (CI 95%: 62-89%). In conclusion, one of the kits is a fast and reliable tool for the iden@fica@on and discrimina@on of M. tuberculosis complex and non-tuberculous mycobacteria from clinical isolates.